Systematic review and meta-analysis protocol for efficacy and safety of Momordica charantia L. on animal models of type 2 diabetes mellitus - Peter, Emanuel L.; Mtewa, Andrew G.; Nagendrappa, Prakash B.; Kaligirwa, Anita; Sesaazi, Crispin Duncan (Systematic Reviews, 2020)
Background: Studies on several preclinical models of type 2 diabetes mellitus have been conducted to establish the hypoglycemic activity of Momordica charantia L. Concerned with appropriateness of these models, we designed a systematic review to establish the efficacy and safety of M. charantia L. in preclinical models of type 2 diabetes mellitus. Methods: Review authors will search without language restriction in MEDLINE/PubMed, Web of Science, Embase, Scopus, and CINAHL databases through April 2019. Search filters will be applied to enhance search efficiency. The authors will search for gray literature in Google and Google Scholar, OpenGrey, and ProQuest Dissertations & Theses. Two authors will evaluate full texts, extract data, and asses risk of bias independently. The review will include randomized or non-randomized studies that assessed the efficacy or safety of M. charantia L. with vehicle control group. The primary endpoint will be fasting blood glucose level. We will use Egger’s test to assess publication biases. Chi-square test and I2 will be used to assess heterogeneity in effect size of the primary outcome. Using RevMan software version 5.3, the authors will perform a meta-analysis of quantitative data. Discussion: The strength of evidence will be rated as high, moderate, low, or very low using GRADE framework for animal studies. This systematic review will potentially improve research practice by identifying risks of bias and design features that compromise translatability and contribute to evidence-based clinical trial design.
Keywords: Diabetes mellitus type 2; Momordica charantia; Animals; Efficacy; Safety; Protocol; Systematic review